The Subject-Object Base of the Integrated System of Economic Security in Modern Conditions - Dobryanskyy, Oleg I. (Bìznes ìnform (Multilingual ed.), 2024)
The article discusses the modern specifics of the formation of the subject-object base of the integrated system of economic security. It is determined that recently there has been a dynamic increase in risks and threats that arise in the sphere of economy and require the formation of effective mechanisms to counteract their interference. The main components of the subject-object base of the integrated system of economic security in modern conditions are analyzed. It is defined that the subject base includes a group of subjects, such as State bodies, enterprises, public organizations and other participants in economic processes. The object base covers objects that need protection, such as information, financial resources, infrastructure, technologies and other components of the economic security system. The practical importance of integration of subject and object bases to ensure the effective functioning of the system of economic security of the State under modern conditions is proved. Various aspects of the integration of the subject-object base are considered, in particular, the development of mechanisms of interaction between subjects, the creation of risk protection systems for objects, and the introduction of innovative approaches to ensuring economic security. The author analyzes the current conditions influencing the system of economic security, in particular globalization, cyber threats and the global security situation. Recommendations for improving the existing subject-object base of economic security have been formed, which provide for the intensive development of cooperation between different subjects, the introduction of modern technologies and the strengthening of cybersecurity with regard to the economic system of the State. It is proved that in modern conditions the subject-object base is a key element of the integrated system of economic security of the State. At that, the integration of subject and object bases requires the use of an integrated approach and the establishment of effective interaction between all stakeholders. It is determined that the development and improvement of the subject-object base is an important task to ensure sustainable development of the national economy and reduce risks to its functioning in the long run.